Spontaneous restoration of functional β‐cell mass in obese SM/J mice. Issue 20 (28th October 2020) - Miranda, Mario A.; Carson, Caryn; St. Pierre, Celine L.; Macias‐Velasco, Juan F.; Hughes, Jing W.; Kunzmann, Marcus; Schmidt, Heather; Wayhart, Jessica P.; Lawson, Heather A.
Abstract: Maintenance of functional β‐cell mass is critical to preventing diabetes, but the physiological mechanisms that cause β‐cell populations to thrive or fail in the context of obesity are unknown. High fat‐fed SM/J mice spontaneously transition from hyperglycemic‐obese to normoglycemic‐obese with age, providing a unique opportunity to study β‐cell adaptation. Here, we characterize insulin homeostasis, islet morphology, and β‐cell function during SM/J's diabetic remission. As they resolve hyperglycemia, obese SM/J mice dramatically increase circulating and pancreatic insulin levels while improving insulin sensitivity. Immunostaining of pancreatic sections reveals that obese SM/J mice selectively increase β‐cell mass but not α‐cell mass. Obese SM/J mice do not show elevated β‐cell mitotic index, but rather elevated α‐cell mitotic index. Functional assessment of isolated islets reveals that obese SM/J mice increase glucose‐stimulated insulin secretion, decrease basal insulin secretion, and increase islet insulin content. These results establish that β‐cell mass expansion and improved β‐cell function underlie the resolution of hyperglycemia, indicating that obese SM/J mice are a valuable tool for exploring how functional β‐cell mass can be recovered in the context of obesity. Abstract : High fat‐fed SM/J mice spontaneously transition from hyperglycemic‐obese to normoglycemic‐obese with age, providing a unique opportunity to study β‐cell adaptation. Here we characterize insulin homeostasis, islet morphology, and β‐cell function during SM/J's diabetic remission.